GABA and glycine neurons from the ventral medullary region inhibit hypoglossal motoneurons. Issue 6 (13th December 2019) - Dergacheva, Olga; Fleury-Curado, Thomaz; Polotsky, Vsevolod Y; Kay, Matthew; Jain, Vivek; Mendelowitz, David
Abstract: Obstructive sleep apnea (OSA) is a common disorder characterized by repetitive sleep-related losses of upper airway patency that occur most frequently during rapid eye movement (REM) sleep. Hypoglossal motoneurons play a key role in regulating upper airway muscle tone and patency during sleep. REM sleep activates GABA and glycine neurons in the ventral medulla (VM) to induce cortical desynchronization and skeletal muscle atonia during REM sleep; however, the role of this brain region in modulating hypoglossal motor activity is unknown. We combined optogenetic and chemogenetic approaches with in-vitro and in-vivo electrophysiology, respectfully, in GAD2-Cre mice of both sexes to test the hypothesis that VM GABA/glycine neurons control the activity of hypoglossal motoneurons and tongue muscles. Here, we show that there is a pathway originating from GABA/glycine neurons in the VM that monosynaptically inhibits brainstem hypoglossal motoneurons innervating both tongue protruder genioglossus (GMNs) and retractor (RMNs) muscles. Optogenetic activation of ChR2-expressing fibers induced a greater postsynaptic inhibition in RMNs than in GMNs. In-vivo chemogenetic activation of VM GABA/glycine neurons produced an inhibitory effect on tongue electromyographic (EMG) activity, decreasing both the amplitude and duration of inspiratory-related EMG bursts without any change in respiratory rate. These results indicate that activation of GABA/glycine neurons from the VM inhibits tongue muscles via a direct pathway to both GMNs and RMNs. This inhibition may play a role in REM sleep associated upper airway obstructions that occur in patients with OSA.